Exploring the Relationship Between Person, Behaviour and Environment in Learning - Wan Suhaifiza, W Ibrahim; Zahari, Abu Bakar; Siti Hazurah, Idnera Putera; Kamaru Adzha, Kadiran; Siti Musliha Ajmal, Mokhtar; Suhaili Beeran, Kutty; Aidil Azli, Alias (RSIS International, 2025)
This study examines the intricate relationship between cognitive, behavioural, and environmental factors in learning, based on Bandura's (1986) social cognitive theory and Wenden & Rubin's (1987) research on learning strategies. Understanding how these elements interact is crucial for enhancing educational practices and student outcomes. The research is set in Johor, Malaysia, focusing on public university students to provide a real-world educational context. The objective is to identify the combined effects of cognitive strategies, behaviour, and environmental management on academic performance. This quantitative study utilized a 5-point Likert scale survey to gather data from 113 respondents. The findings indicate that effective cognitive and behavioural strategies and well-managed learning environments significantly enhance student performance. The study's implications suggest that integrating these strategies into educational practices and fostering supportive environments can improve academic outcomes. This research highlights the need for a holistic approach to learning, emphasizing the interplay of cognitive, behavioural, and environmental factors.